The nature and development of the construct “quality of work life” - Tina Kotzé (Acta Academica, 2005)
Major changes have taken place in the nature and composition of organisations in South Africa. The greater importance of knowledge workers, the different ethnic composition of the membership of organisations, and changes in value systems and beliefs may be seen as factors influencing the quality of employees’ work life (QWL). There is a significant lack of clarity regarding QWL as a construct, and no single instrument to promote consistency in its measurement. This article therefore attempts to provide more information on the content of the construct by means of a literature review. The origin and development of the construct, as well as the different approaches taken to define and measure it, are discussed. QWL emerges as a multifaceted and ambiguous construct with no universal identity. How it is defined, how to approach or measure it appear to depend on the goals of the various researchers and management practitioners.